PENGARUH PROMOSI PENJUALAN DENGAN PENDEKATAN TRANSAKSIONAL DAN PENDEKATAN NEURO LINGUISTIC PROGRAM TERHADAP MINAT DAN KEPUTUSAN DOKTER DALAM MEMILIH PRODUK DAN IMPLIKASINYA UNTUK PENULISAN RESEP - Prihatini, Indri; Sumaryono, Wahono; Bahfen, Faiq (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
Interests are regarded as an intermediary between motivational factors that influencebehavior and indicate how hard a person has a willingness to Interests shows howmuch effort a person is planning to do something in order to produce a decision.Purchasing decisions are a step in the decision-making process in which theconsumer actually makes a purchase. One of the factors that influence the interest ofdoctors to make decisions in prescribing drugs in the hospital is the approachbetween a medical representative with a doctor. This study aims to determine theeffect of promotion with a transactional approach and neuro linguistic approachprogram (NLP) to the decision of the physician in choosing a product and itsimplications for prescription writing. The sample in this research is doctors whowork in Hospital in Jakarta area, amount 80 responder determined by formula Slovin.The type of data used is the primary data taken through the questionnaire. Theanalysis method used is multiple linear regression with doctor's decision inprescribing as dependent variable, while the independent variable is sales promotionin transactional and sales promotion in NLP. The results showed that the mostinfluential factor on physician interest in decision making on prescription writingwas sales promotion in NLP with 33.2% contribution, compared to transactionpromotion transactional which only 5.3%. Therefore, NLP can be a good choice forsales promotion of physicians' interest and decisions in prescribing.